Use of Digitization in Chemical Enterprises - Vávra, Jan; Spáčil, Petr; Bakeš, Oskar (Česká společnost průmyslové chemie, 2022)
Industrial transformation and especially the digitization of business processes is a prerequisite for maintaining competitiveness, across industries. However, the use of digitization Key Enabling Technologies (KETs) differs in the mechanical, process, and hybrid industries. The chemical industry, as a typical representative of process production, differs significantly, especially in the possibilities of product monitoring or in the operation of production equipment. No significant impact of digitization on raw material purchasing, logistics, research, and development processes is expected. Perceived benefits, on the other hand, are expected in production, sales & marketing, and administration processes. To confirm these starting points and verify the state and perception of the importance of digitization in the Czech Republic among chemical production companies, research was carried out in selected chemical companies. Areas and processes in which digitization is already developing have been identified, as well as obstacles and barriers to a faster transformation of the chemical industry according to the Industry 4.0 concept.
Využití digitaliazce v chemických podnicích
Keywords: Industry 4.0; digitization; chemical enterprises; Průmysl 4.0; digitalizace; chemické podniky